The Swiss Cheese Mutant Causes Glial Hyperwrapping and Brain Degeneration in Drosophila - Kretzschmar, Doris (J Neurosci, 1997)
Swiss cheese (sws) mutant flies develop normally during larval life but show age-dependent neurodegeneration in the pupa and adult and have reduced life span. In late pupae, glial processes form abnormal, multilayered wrappings around neurons and axons. Degeneration first becomes evident in young flies as apoptosis in single scattered cells in the CNS, but later it becomes severe and widespread. In the adult, the number of glial wrappings increases with age. The sws gene is expressed in neurons in the brain cortex. The conceptual 1425 amino acid protein shows two domains with homology to the regulatory subunits of protein kinase A and to conceptual proteins of yet unknown function in yeast, worm, and human. Sequencing of two sws alleles shows amino acid substitutions in these two conserved domains. It is suggested that the novel SWS protein plays a role in a signaling mechanism between neurons and glia that regulates glial wrapping during development of the adult brain.